Correction: Biogeography of the endosymbiotic dinoflagellates (Symbiodiniaceae) community associated with the brooding coral Favia gravida in the Atlantic Ocean. - Mariana M Teschima; Amana Garrido; Alexandra Paris; Flavia L D Nunes; Carla Zilberberg (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0213519.].